A search and matching approach to business-cycle migration in the euro area - Janine Hart; Marius Clemens (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Recently migration patterns in the euro area changed markedly in response to increasing unemployment disparities. This reinforced the interest in labor mobility as stabilization tool against the background of heterogeneous labor market conditions. In a data set of 55 bilateral migration corridors in the euro area over the period 1980-2010 we find evidence for business-cycle related fluctuations in net migration flows and the crucial role of unemployment and vacancies in shaping migration patterns. We propose a two-country DSGE model with migration that is able to replicate the empirical facts on business-cycle migration. In this model unemployment arises from search and matching frictions. We endogenize migration via the unemployed workers choice on which labor market to search for a job. The framework allows to account for wage and unemployment gaps between natives and immigrants over the cycle as well as for factors such as language barriers that hinder the labor market integration of foreigners. We find that the impact of migration on country-specific average wages and unemployment depends crucially on the characteristics of immigrants and natives as well as the institutional characteristics of the total corridor, i.e. search efficiency. The model will be used to analyze the effects of different immigration and labor market policies on migration patterns and welfare.
Keywords: J61; 330; Labor Migration; Unemployment; Search and Matching